Thermodynamics of an OWC containing real gas. (15th September 2017) - Medina-López, E.; Moñino, A.; Borthwick, A.G.L.; Clavero, M.
Abstract: Oscillating Water Column (OWC) devices are usually modelled as simple systems containing ideal, dry air. However, high humidity levels are likely to occur in a prototype device open to the sea, particularly in warm climates such as prevail in the lower latitudes. In this paper, a real gas model is implemented to take into account humidity variations inside an OWC chamber. Using a modified adiabatic index, theoretical expressions are derived for the thermodynamic state variables including enthalpy, entropy and specific heat. The model is validated against experimental data, and shown to provide better agreement than obtained using the ideal gas assumption. By calculating real air flow in an OWC it is shown that the mechanical efficiency reduces and the flow phase alters with respect to the ideal gas case. Accurate prediction of efficiency is essential for the optimal design and management of OWC wave energy converters. Highlights: This paper studies the Thermodynamics of Oscillating Water Column (OWC) systems. A real gas model is presented to analyse the real working conditions of an OWC. Humidity, pressure and temperature changes in the OWC chamber are considered. A validation of the real gas model is presented and compared with ideal gas theory. Differences up to 6% in efficiency between ideal and real gas models are observed.